2005
DOI: 10.1017/s0016756804000366
|View full text |Cite
|
Sign up to set email alerts
|

Cambrian biostratigraphy of the Tal Group, Lesser Himalaya, India, and early Tsanglangpuan (late early Cambrian) trilobites from the Nigali Dhar syncline

Abstract: Precise biostratigraphic constraints on the age of the Tal Group are restricted to (1) a basal level correlative with the Anabarites trisulcatus–Protohertzina anabarica Assemblage Zone of southwest China, (2) a level near the boundary of the lower and upper parts of the Tal Group correlative with the early Tsanglangpuan Stage (Drepanuroides Zone), and (3) an interval low in the upper part of the Tal Group correlative with later in the Tsanglangpuan Stage (Palaeolenus Zone). These correlations are based on smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 106 publications
(88 citation statements)
references
References 41 publications
(50 reference statements)
3
85
0
Order By: Relevance
“…The fossils are represented by mollusc-like shells, such as cyrtoconic planispiral Oelandiella Vostokova, 1962 andsinistrally coiled Barskovia Golubev, 1976, conchs of hyoliths, siphogonuchitid sclerites and scaly shells of Purella Missarzhevsky, 1974. The earliest hyoliths are also described from the probably time-equivalent basal Purella Zone of Western Mongolia , SSF1 of South China (Qian & Bengtson, 1989;Steiner et al 2004a) and India (Brasier & Singh, 1987;Hughes et al 2005). Siphogonuchitid sclerites and shells of Maikhanella Zhegallo in Voronin et al 1982 are also reported from SSF1 beds of South China (Qian & Bengtson, 1989;Steiner et al 2004a), whereas Purella defines the base of the Purella Zone in Western Mongolia Fig.…”
Section: D Molluscs Hyoliths Halwaxiids and Chancelloriidsmentioning
confidence: 98%
See 1 more Smart Citation
“…The fossils are represented by mollusc-like shells, such as cyrtoconic planispiral Oelandiella Vostokova, 1962 andsinistrally coiled Barskovia Golubev, 1976, conchs of hyoliths, siphogonuchitid sclerites and scaly shells of Purella Missarzhevsky, 1974. The earliest hyoliths are also described from the probably time-equivalent basal Purella Zone of Western Mongolia , SSF1 of South China (Qian & Bengtson, 1989;Steiner et al 2004a) and India (Brasier & Singh, 1987;Hughes et al 2005). Siphogonuchitid sclerites and shells of Maikhanella Zhegallo in Voronin et al 1982 are also reported from SSF1 beds of South China (Qian & Bengtson, 1989;Steiner et al 2004a), whereas Purella defines the base of the Purella Zone in Western Mongolia Fig.…”
Section: D Molluscs Hyoliths Halwaxiids and Chancelloriidsmentioning
confidence: 98%
“…The first occurrences of skeletonized bilaterians within the Parabadiella and Eoredlichia-Wutingaspis zones of the Qiongzhusian Stage are biostratigraphically correlated (but not directly constrained by chemostratigraphy) with the middle-upper Atdabanian and upper Atdabanianlower Botoman stages of Siberia, respectively (Qian et al 2002;Li et al 2007;Li & Xiao, 2004;Steiner et al 2007;Fig. 3 Brasier & Jiang, 1989;Hamdi, 1995;Hughes et al 2005). The three regions belonged to East Gondwana (Fig.…”
Section: D South China India and Iranmentioning
confidence: 99%
“…West of Nepal, the Tons Thrust divides the Indian LH into "inner" (iLH) and "outer" (oLH) zones (Valdiya, 1980;Ahmad et al, 2000) with oLH rocks sitting in the hanging wall of the Tons Thrust and iLH rocks in the footwall (Célérier et al, 2009a(Célérier et al, , 2009bWebb et al, 2011b;Webb, 2013). Presently, strata from only the upper LH succession have been confirmed in the oLH, most of which range from Cryogenian to Cambrian in age (Jiang et al, 2002;Hughes et al, 2005;Célérier et al, 2009a;McKenzie et al, 2011). iLH rocks include two main structural units, the Damtha-Deoban duplex and the Berinag Thrust sheet.…”
Section: Geologic Backgroundmentioning
confidence: 99%
“…The northern margin of the Indian plate (Tethyan Himalaya) owing to its position in the core Gondwanaland constitutes significant link to decipher the evolution of the Phanerozoic history during the assembly of the Gondwanaland. Precise biostratigraphic constraints on the Cambrian of the Himalaya show that the Tethyan and the Lesser Himalayan regions are closely comparable to the southwest China Basin, strengthening the recent suggestion for close geographic proximity between the Himalaya and the Yangtze block during late Neoproterozoic through Early Cambrian time (Hughes et al 2005). During the Cambrian period, the Indian continent lay 20° N of the equator and formed the western part of the Gondwana surrounded by the perigondwanian microcontinents.…”
Section: Cambrian Fauna and P Aleobiogeographic Affinitymentioning
confidence: 74%
“…The identification of the distinctive late Early Cambrian trilobites Dolerolenus (Malungia) laeivigata, Drepanopyge, and Protolenella from the Lesser Himalaya (Hughes et al 2005) and their correlation with Yangtze block of southwest China (Luo, Jiang and Tang, 1994) and Kunming region (Zhou and Yuan, 1980) is also significant as it shows proximity of the Indian block with that of Yangtze platform during the Neoproterozoic and Early Cambrian time (Hughes et al 2005). In the Zanskar region so far no body fossils of Early Cambrian have been recorded, therefore, the paleogeographic reconstruction of this region is uncertain for the Early Cambrian stage.…”
Section: Early Cambrianmentioning
confidence: 99%